2022
DOI: 10.1111/ocr.12595
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional comparison of bone‐borne and tooth‐bone‐borne maxillary expansion in young adults with maxillary skeletal deficiency

Abstract: Objective To compare the transverse dental and skeletal changes in patients treated with bone‐anchored palatal expander (bone‐borne, BB) compared to patients treated with tooth and bone‐anchored palatal expanders (tooth‐bone‐borne, TBB) using cone‐beam computer tomography (CBCT) and 3D image analysis. Methods The sample comprised 30 patients with transverse maxillary discrepancy treated with two different types of appliances: bone‐borne (Group BB) and tooth‐bone‐borne (Group TBB) expanders. CBCT scans were acq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 30 publications
4
11
0
Order By: Relevance
“…According to this study's findings, an increase in IDDM1 in CH as compared to HH due to increase the tipping effect in CH, this was in agreement with Gunyuz et al 3 , Bazzani et al 24 and Martina et al 27 . On the other side this was in disagreement with Pasqua et al 38 since maxillary width showed significant difference between groups, increasing more in HHG than conventional one, this might attributed to different design of the appliance with different age group.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…According to this study's findings, an increase in IDDM1 in CH as compared to HH due to increase the tipping effect in CH, this was in agreement with Gunyuz et al 3 , Bazzani et al 24 and Martina et al 27 . On the other side this was in disagreement with Pasqua et al 38 since maxillary width showed significant difference between groups, increasing more in HHG than conventional one, this might attributed to different design of the appliance with different age group.…”
Section: Discussionsupporting
confidence: 92%
“…1,2 In a growing patient, RPE successfully opens the midpalatal suture using a conventional hyrax(CH). 3 Because RPE is frequently coupled with high force 4 , there is a danger of root resorption 5 and bone dehiscence of the anchored teeth. 6 Some authors believe that with the introduction of bone-borne maxillary expansion, a few risks to anchored teeth have been avoided 7,8 , while other studies found no change.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, asymmetry of miniscrew position changes was observed: both left screws showed a greater amount of displacement and angular variation when compared to the opposite side; this observation suggests a greater stability loosening on the left side in respect to the right side. These results can be related to the asymmetrical skeletal expansion results observed in a previous study, where the right side showed more displacement when compared to the left side [ 19 ].…”
Section: Discussionsupporting
confidence: 66%
“…This pyramidal pattern suggests a reason why the expansion screw opening, which occurs at a lower height with respect to the pyramid vertex, is greater than the suture opening measure. However, in a more recent study it was observed that bone-borne expansion of the maxilla did not follow the pyramidal pattern reported in previous studies, with similar amounts of skeletal expansion observed at orbitale, zygoma and nasal cavity [ 19 ].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation